Phosphorylation of the N-methyl-d-aspartate receptor is increased in the nucleus accumbens during both acute and extended morphine withdrawal - Anderson, Ethan M. (J Pharmacol Exp Ther, 2015)
Opioid withdrawal causes a dysphoric state that can lead to complications in pain patients and can propagate use in drug abusers and addicts. Opioid withdrawal changes the activity of neurons in the nucleus accumbens, an area rich in both opioid-binding mu opioid receptors and glutamate-binding NMDA receptors. Because the accumbens is an area important for reward and aversion, plastic changes in this area during withdrawal could alter future behaviors in animals. We discovered an increase in phosphorylation of serine 897 in the NR1 subunit of the NMDA receptor (pNR1) during acute morphine withdrawal. This serine can be phosphorylated by protein kinase A (PKA) and dephosphorylated by calcineurin. We next demonstrated that this increased pNR1 change is associated with an increase in NR1 surface expression. NR1 surface expression and pNR1 levels during acute withdrawal were both reduced by the NMDA receptor antagonist MK-801 (dizocilpine hydrogen maleate) and the PKA inhibitor H-89(N-[2-[[3-(4-bromophenyl)-2-propenyl]amino]ethyl]-5-isoquinolinesulfonamide dihydrochloride hydrate). We also found that pNR1 levels remained high after an extended morphine withdrawal period of 2 months, correlated with reward-seeking behavior for palatable food, and were associated with a decrease in accumbal calcineurin levels. These data suggest that NR1 phosphorylation changes during the acute withdrawal phase can be long lasting and may reflect a permanent change in NMDA receptors in the accumbens. These altered NMDA receptors in the accumbens could play a role in long-lasting behaviors associated with reward and opioid use.